2018
DOI: 10.22437/bio.v4i2.6127
|View full text |Cite
|
Sign up to set email alerts
|

Authentic Assessment Analysis Based on the Curriculum 2013 at SMP Negeri 7 Muaro Jambi

Abstract: The 2013 curriculum requires the use of authentic assessment, where students are assessed for their readiness, process, and learning outcomes as a whole. This research was conducted at Muaro Jambi 7 Junior High School which aimed to find out the implementation of authentic assessment  subjects at Muaro Jambi Junior High School and to find out whether authentic assessment was carried out properly or not. Data collection methods used in the study are documentation studies, interviews and questionnaires. Subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…The finding of this study together with those of the previous ones shows that in authentic assessment, there are still some constraints on the teachers so they did not do this assessment optimally. In line with this finding, the research by Agustina et al (2018) also had the same finding, that in the process of authentic assessment, there were several constraints, including too many assessment formats the teachers had to make in the so limited time so that they could not do authentic assessment optimally. These constraints certainly need solution.…”
Section: Discussionsupporting
confidence: 54%
“…The finding of this study together with those of the previous ones shows that in authentic assessment, there are still some constraints on the teachers so they did not do this assessment optimally. In line with this finding, the research by Agustina et al (2018) also had the same finding, that in the process of authentic assessment, there were several constraints, including too many assessment formats the teachers had to make in the so limited time so that they could not do authentic assessment optimally. These constraints certainly need solution.…”
Section: Discussionsupporting
confidence: 54%
“…Schools are required to develop reliable and credible student assessments to be the policies that surround them. Alimuddin's (2014) research revealed that schools that neglected assessment impacted students' potential creation and poor quality standards. Assessment is seen as the input obtained from the learning process that can determine the strengths and weaknesses of the various components contained in a learning process (McGrew et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Masrul's (2015) study in Riau evaluated students' writing abilities in learning English with a descriptive approach. In addition, Agustina et al (2018) research in Jambi on the analysis of authentic assessment based on the 2013 curriculum in schools with a qualitative approach. This study sees that the assessments that occur still need improvement, especially in the affective and psychomotor aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Masrul's [9] study in Riau on evaluating students' writing abilities in learning English with a descriptive approach. In addition, Agustina, et al [10] research in Jambi on the analysis of authentic assessment based on the 2013 curriculum in schools with a qualitative approach. This study sees that the assessments that occur still need improvement, especially in the apective and psychomotor aspects.…”
Section: Introductionmentioning
confidence: 99%